Neuroendokrine Tumoren im Gastrointestinaltrakt - Breitling, Lutz Philipp; Rinke, Anja; Gress, Thomas Mathias (DMW - Deutsche Medizinische Wochenschrift, 2019)
Neuroendocrine neoplasms (NEN) are increasingly diagnosed tumors with great clinical and prognostic heterogeneity. One of the peculiarities of NEN is the presence of a clinical hormone syndrome in about 30 % of cases. Somatostatin receptor imaging plays an important role in the diagnosis of spreading and in the planning of therapy. NEN patients should be co-supervised by specialized centers and if possible treated as part of studies. In the case of NEN with no or only circumscribed metastases, complete resection in curative intention is generally the highest therapeutic goal. Small neuroendocrine tumors (NET) G1 of the stomach, duodenum and rectum can be curatively endoscopically resected. In the case of a metastatic, non-curative disease, an antiproliferative therapy with the aim of growth control takes place. In patients with functionally active tumors, an antisecretory or symptomatic therapy is used to control the hormone syndrome. The treatment of metastatic NET is often multimodal and must be established by an experienced interdisciplinary team. The prognosis of NEN is mainly determined by the stage at the time of diagnosis, tumor differentiation, grading and localization of the primary tumor.
Keywords: neuroendokrine Neoplasie; Somatostatin-Rezeptor-Bildgebung; Somatostatin-Analoga; multimodale Therapie